Entrepreneurship in tourism - Walmsley, Andreas, ....- (Abingdon, Oxon ; : Routledge, 2019)
"The development of tourism has historically been characterised by enterprising individuals. Small businesses are the backbone of the tourism and hospitality industry. However, entrepreneurship and the entrepreneurial process have long been marginal topics within tourism scholarship. This is a critical, yet accessible, introduction to the subject. Structured into twelve chapters, this book takes an intuitive step-by step progression through entrepreneurship in tourism: context, theoretical perspectives and definitions; the entrepreneurial process from concept to reality; the business plan; marketing, employment and strategy to growth, policy context and future directions. Featuring learning outcomes, 'reflective practice' activities and a range of international case studies that encourage critical thinking and practical applications, this is essential reading for anyone studying tourism degree programmes at undergraduate and graduate level"--
Entrepreneurship in tourism : an introduction -- Conceptual foundations of entrepreneurship -- Innovation -- Initial steps : the role of the business plan -- Marketing -- From birth to growth -- Entrepreneurship and employment -- Strategy and entrepreneurship -- Social entrepreneurship in tourism -- Public policy and entrepreneurship in tourism -- Contemporary issues in entrepreneurship research.
Includes bibliographical references and index.
Keywords: Entrepreneurship ; tourism; Toerisme ; management; Tourism : management